THE INFLUENCE OF BABY SPA ON SLEEP QUALITY IN BANTARJAYA VILLAGE, PEBAYURAN DISTRICT, BEKASI REGENCY IN 2023 - Ika Kania Fatdo Wardani (NHM PRESS, 2023)
Baby spa is one fun way to relieve tension and feelings of restlessness, especially in babies. The initial survey was conducted by researchers in Bantarjaya Village in October through interviews with 3 mothers who stated that they did not know the benefits of baby spa, babies had not been done baby spa, and experienced sleep disorders. The goal is to determine the effect of baby spa on sleep quality. The research method uses quantitative methods (Quasi-Experiment), Wilcoxon's statistical test. The population is all mothers who have babies aged 3-6 months in Bantarjaya Village as many as 47 people. The sample was mothers who had babies aged 3-6 months in Bantarjaya Village using total sampling techniques, as many as 47 people. Data collection by questionnaire. Data analysis is a univariate, bivariate analysis. The results showed that from 47 babies, after a baby spa the babies experienced an increase in sleep quality (sound) by 29.8%. The results of statistical tests are known to Asymp. Sig is 0.000 (P < 0.05), so it can be concluded that there is a difference or influence of baby spa with sleep quality in infants aged 3-6 months.